Interactive formula for fire resistance of columns - Tang, Chuyang. (2008)
This study aims to develop a simple and unified analytical method for predicting fire resistance of steel, reinforced concrete (RC), and concrete filled steel (CFS) columns under fire conditions. The effects of elevated temperatures on material deterioration, and thus strength and stability of columns, are assessed, which leads to a simple but powerful method – the Rankine method.